Closing the artificial intelligence skills gap in construction: competency insights from a systematic review - Lovelin Ifeoma Obi; Innocent Chigozie Osuizugbo; Bankole Osita Awuzie (Results in Engineering)
The integration of Artificial Intelligence (AI) into the construction industry is transforming traditional practices and demanding a new set of competencies from professionals. However, a comprehensive understanding of the specific skills required remains limited. Addressing this gap, a systematic literature review and meta-analysis is conducted in this study to identify and synthesise the AI-related skillsets essential for construction professionals to effectively integrate AI into project delivery. Employing the PRISMA framework and scientometric analysis using VOSviewer, the study analysed 17 key publications sourced from multiple academic databases. The findings reveal eight core AI skill domains: Data Literacy and Management, AI and Machine Learning Fundamentals, Programming and Computation, Digital Collaboration Tools, AI-Driven Decision Making, Cybersecurity Awareness, Change Management and Adaptability, and Communication and Collaboration. The study also highlights a global disparity in research contributions, with notable under-representation from Africa and North America. These insights underscore the urgent need for targeted training, policy development, and collaborative research to bridge the AI skills gap in the construction sector. In addition, the study reveals that, the underdevelopment of AI skills among construction professionals is shaped by a complex interplay of educational, cultural, infrastructural, economic, policy-related, and industry-specific factors. This review provides a foundational roadmap for developing initiatives aimed at equipping construction professionals with the competencies necessary to thrive in an AI-enhanced built environment.